Non‐Animal Strategies for Toxicity Assessment of Nanoscale Materials: Role of Adverse Outcome Pathways in the Selection of Endpoints. Issue 15 (9th February 2021) - Halappanavar, Sabina; Nymark, Penny; Krug, Harald F.; Clift, Martin J. D.; Rothen‐Rutishauser, Barbara; Vogel, Ulla
Abstract: Faster, cheaper, sensitive, and mechanisms‐based animal alternatives are needed to address the safety assessment needs of the growing number of nanomaterials (NM) and their sophisticated property variants. Specifically, strategies that help identify and prioritize alternative schemes involving individual test models, toxicity endpoints, and assays for the assessment of adverse outcomes, as well as strategies that enable validation and refinement of these schemes for the regulatory acceptance are needed. In this review, two strategies 1) the current nanotoxicology literature review and 2) the adverse outcome pathways (AOPs) framework, a systematic process that allows the assembly of available mechanistic information concerning a toxicological response in a simple modular format, are presented. The review highlights 1) the most frequently assessed and reported ad hoc in vivo and in vitro toxicity measurements in the literature, 2) various AOPs of relevance to inhalation toxicity of NM that are presently under development, and 3) their applicability in identifying key events of toxicity for targeted in vitro assay development. Finally, using an existing AOP for lung fibrosis, the specific combinations of cell types, exposure and test systems, and assays that are experimentally supported and thus, can be used for assessing NM‐induced lung fibrosis, are proposed. Abstract : AOPs enable the systematic organisation of the existing in silico, in vivo and in vitro toxicology data (specific to NM or non‐NM data) and serve as mechanistic backbones for the establishment of potential animal reduction or replacement strategies and toxicity testing tools. Together with the information on material characterisation and exposure, they enable derivation of risk indicators.